2016
DOI: 10.4317/medoral.21170
|View full text |Cite
|
Sign up to set email alerts
|

Paranasal sinuses malignancies: A 12-year review of clinical characteristics

Abstract: BackgroundInadequate epidemiologic investigations of the paranasal sinuses malignancies prompted this retrospective study with special emphasis on a major group of 111 tumors.Material and MethodsClinical records of 111 patients with histologically confirmed malignant tumors of the paranasal sinuses were investigated retrospectively from April 2000 to January 2012. Collection of data included demographic information, clinical manifestations, treatment plans, and histopathology of the tumor.ResultsThere were 69 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 21 publications
8
26
0
Order By: Relevance
“…Such a locally aggressive disease emphasizes the importance of improving local therapy. Local disease recurrence has been reported as a predominant treatment failure pattern in the literature . This also is supported by the findings presented herein that patients with surgically accessible tumors fared better.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Such a locally aggressive disease emphasizes the importance of improving local therapy. Local disease recurrence has been reported as a predominant treatment failure pattern in the literature . This also is supported by the findings presented herein that patients with surgically accessible tumors fared better.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with published retrospective series, the majority of patients presenting with sinonasal cancer were male, were non‐Hispanic white, and had squamous cell histology . The results of the current study also demonstrated worse outcomes for African American patients and improved outcomes for Hispanic patients compared with non‐Hispanic white patients.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations